Sarawak Baitulmal Management System using SMS Notification (SBMS) / Farina Yasmin Abdul Manap … [et al.] - Abdul Manap, Farina Yasmin; Ahmad Jais, Siti Nurlina; Amri, Muhammad Amirul; Hafizul Azly, Muhamad Luqman Hakim; Abdul Rahid @ Abdul Rashid, Nurul Najwa (Faculty of Computer and Mathematical Sciences, 2021)
Previously, the application submitted by the candidate in hardcopy form. Then, the form will then manually process one by one by the staffs and they will insert every information in the application form into an Excel database. Then after confirming whether the application failed or qualified, the form will be sends out to HQ in Kuching, Sarawak using ‘Poslaju’ service. Lastly, for data keeping, the forms will be copied and stored in files according to the reference number. After the online system has been implemented, the candidates are still submitting their application like before and the staff will fill in their information into the database. But the current system has flaws which delays the time of each applications to be processed. The current system does not store the candidate’s data from their last application which made the staffs had to fill in the same info repeatedly. The system also does not have an automated SMS notification that will inform the candidates regarding their application status. Therefore, the main objective for this project is to develop a web application Sarawak Baitulmal management system with SMS notification. The output of the system can be seen by the SMS notification that is sent to candidate’s phone number to inform about their application status.